In moderation of 'strangers': terrorism, ontological (In)security and counter-narratives in Malaysia. Issue 1 (2nd January 2020) - Chan, Nicholas
ABSTRACT: Counter-narratives is a celebrated strategy in countering violent extremism (CVE), but critical study of its contents is still lacking. This paper not only examines such narratives directly through mostly non-English materials published by Malaysian state agencies, it also proposes a new framework to understand them. It argues that these narratives perform an ontological security-seeking function by the Muslim state when faced with the dilemma of the jihadist terrorist as 'stranger', that is, a violator of insider/outsider, friend/enemy, civilian/militant categories that are key to the state's sense of self-identity. Unable to securitise the Muslim terrorist as an 'evil' outsider, counter-narratives demystify the 'stranger-terrorist' in making the constitutive qualities of 'violent extremism' legible, detectable, and therefore governable. Through these discourses of biopolitics and Islamic hermeneutics, the Muslim state reclaims its ontological certainty by reasserting normative and self-referential claims about state, Islam, and Muslim subjectivity-claims that are under profound challenge by the anti-systemic nature of transnational jihadist terrorism. In reconceptualising counter-narratives beyond technocratic terms, this paper reveals the productive nature of counter-terror enterprises through its intertwining with governance, identity, order, and ontological security.